2023
DOI: 10.1039/d3em00014a
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal trends and characteristics of microplastic contamination in a large river-dominated estuary

Abstract: Microplastics (MPs) are emerging contaminants in aquatic ecosystems and have caused substantial concern worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…C 0i is a defined value that is symbolized in the study by the lowest concentration of microplastics present in each sampling site. 36 The microplastic ecological risk index is evaluated using the PLI, which represents the load index of microplastics on the basis of MP concentration. A list of MP criteria, presented in Table S3,† defines the level of risk associated with polymers.…”
Section: Methodsmentioning
confidence: 99%
“…C 0i is a defined value that is symbolized in the study by the lowest concentration of microplastics present in each sampling site. 36 The microplastic ecological risk index is evaluated using the PLI, which represents the load index of microplastics on the basis of MP concentration. A list of MP criteria, presented in Table S3,† defines the level of risk associated with polymers.…”
Section: Methodsmentioning
confidence: 99%
“…MP pollution is a problem that has gained international attention from scientists, the research community, the general public, and society. However, it has been noted that these tiny particles are present in all of the biotic and environmental elements, specifically, rain runoff, food products, dust, soil, atmosphere, groundwater, surface water, river water, sediment, and so on. With their omnipresence, high inertness, and stability, it is clear that these particles could have a negative impact on both the environment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fate and behavior of MPs in marine ecosystems has been widely studied, the transport and sedimentation processes of MPs in freshwater bodies is still not fully understood. Several studies have identified high accumulations of MPs in specific depositional areas of freshwater bodies, such as rivers [16,18,19], lakes [17,20], and dam reservoirs [4,[21][22][23][24]. Moreover, Horton et al [25] indicated that in artificial aquatic environments, the accumulation of MPs is more complicated than in completely natural systems due to the complex interaction of natural-artificial factors.…”
Section: Introductionmentioning
confidence: 99%